Multitemporal water quality study in Sitjar (Castelló, Spain) reservoir using Sentinel-2 images - C. Radin; X. Sòria-Perpinyà; J. Delegido (Revista de teledetección, 2020)
Water quality is a subject of intense scientific inquiry because of its repercussion in human’s life, agriculture or even energy generation. Remote sensing can be used to control water masses by analyzing biophysical variables. Chlorophyll-a (Chl-a) and Total Suspended Solids (SS) are a well-known feature of water quality. These variables have been measured in Sitjar reservoir (Castelló, Spain) as a part of the project Ecological Status of Aquatic Systems with Sentinel Satellites (ESAQS), in order to compare the results with satellite reflectance data. Two processes were compared to correct atmospherically the level 1C Sentinel 2 (S2) images. The results show that Case 2 Regional Coast Colour (C2RCC) method, with a Root Mean Square Error of 2.4 mg/m3 (Chl-a) and 3.9 g/m3 (SS) is a better tool for atmospheric correction in this scenario due to the low turbidity levels of water. Besides, in this paper we study the Chl-a and SS variability through April 2017 to March 2019 with fourteen S2 images with the automatic products from C2RCC correction, finding correlations between them and the climate and reservoir conditions. Chl-a increase from 0.4 mg/m3 to 9.5 mg/m3 while SS rise 18 g/m3 in this period, which makes Sitjar as an oligotrophic-mesotrophic system. The correlation results demonstrate an excellent correspondence between them (R2=0.9). Sitjar reservoir lost almost 40 hm3 at the beginning of the study, which it had a possible relationship with the increasing parameter values. Also discussed was the role played by the climatology in the reservoir conditions due to the changes in the water structure with seasons, which explains the ariability through the year.